2017
DOI: 10.1055/s-0036-1588708
|View full text |Cite
|
Sign up to set email alerts
|

Cyclocarbopalladation as a Key Step in Cascade Reactions: Recent Developments

Abstract: Cascade reactions are step-economical processes for the synthesis of complex molecules as they allow, in one step, the formation of multiple bonds. Over the last two decades cyclocarbopalladation has emerged as a powerful key step when integrated into these sequences and has allowed unprecedented valuable polycyclic scaffolds to be obtained. This review is focused on recent developments in this field including original cascade sequences, novel activation modes (C-H activation for instance) and unprecedented fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(1 citation statement)
references
References 73 publications
0
0
0
Order By: Relevance
“…Malonate deprotonation by sodium hydride, followed by allylation with 2,3-dibromopropene, gave the monoallylated product. Further deprotonation by sodium hydride and treatment with excess propargyl bromide Previous work from our group [15,16] demonstrated that this type of cascade can indeed be used to synthesize 7,8 systems (8, Figure 1b), and indeed carbopalladation/coupling/ electrocyclisation sequences are generally well-established [17][18][19][20]. However, we aimed to avoid the use of a toxic organotin coupling partner as had been employed in our previous work [15,16] by switching to an untested Suzuki/8π strategy.…”
Section: Synthesis Of 56-fused Systems By Bromoenynamide Carbopallada...mentioning
confidence: 99%
“…Malonate deprotonation by sodium hydride, followed by allylation with 2,3-dibromopropene, gave the monoallylated product. Further deprotonation by sodium hydride and treatment with excess propargyl bromide Previous work from our group [15,16] demonstrated that this type of cascade can indeed be used to synthesize 7,8 systems (8, Figure 1b), and indeed carbopalladation/coupling/ electrocyclisation sequences are generally well-established [17][18][19][20]. However, we aimed to avoid the use of a toxic organotin coupling partner as had been employed in our previous work [15,16] by switching to an untested Suzuki/8π strategy.…”
Section: Synthesis Of 56-fused Systems By Bromoenynamide Carbopallada...mentioning
confidence: 99%